Preparation method of chopped carbon fiber reinforced SiC ceramic

By introducing chopped carbon fibers into SiC ceramics and using boron-modified phenolic resins, the problems of poor brittleness and reliability of SiC ceramic materials are solved, and the high strength and toughness of the material are achieved, which is suitable for high-temperature structural and functional materials.

CN119638464APending Publication Date: 2025-03-18UNIV OF SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411746909.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The poor brittleness and reliability of SiC ceramic materials limit its long-term development in the fields of machinery, aviation, aerospace, etc.

Method used

By introducing chopped carbon fibers into SiC ceramics and using boron-modified phenolic resin as sintering additives, the introduction method of ceramic additives is adjusted to promote the densification of ceramic sintering.

Benefits of technology

It significantly improves the flexural strength and sintering density of SiC ceramics, improves the brittleness and reliability of the material, making it more suitable for high-temperature structural and functional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638464A_ABST
    Figure CN119638464A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of chopped carbon fiber reinforced SiC ceramic, and relates to the technical field of novel materials. By adjusting the introduction mode of the ceramic additive, ceramic sintering densification is greatly influenced, boron modified phenolic resin is adopted as the modified phenolic resin, boron can selectively segregate at the silicon carbide grain boundary, the grain boundary energy is reduced, the ratio of the grain boundary energy to surface energy is reduced, and sintering is promoted; meanwhile, the boron element can be dissolved in silicon carbide crystal lattices to generate lattice defects, so that the diffusion coefficient is increased, and the sintering compactness of the ceramic is promoted; carbon can reduce an oxide layer on the surface of the silicon carbide micro-powder, improve the surface energy of the micro-powder and improve the sintering driving force; the modified phenolic resin realizes dispersion of boron and carbon at a molecular level, so that the boron and the carbon can uniformly coat the surfaces of the carbon fibers and the silicon carbide micro powder, the sintering promotion effect of the boron and the carbon is effectively exerted, air holes in the ceramic are favorably removed, and the sintering density of the ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a method for preparing chopped carbon fiber reinforced SiC ceramics. Background Art

[0002] Composite materials are a new type of material produced by combining two or more substances through certain means. This material can have the excellent properties of several substances at the same time and minimize the shortcomings of the substances involved in the combination, so that the newly produced material in the form of composite has new characteristics and new functions.

[0003] Among the non-metallic matrices of composite materials, silicon carbide (SiC) ceramics are a ceramic material with a series of excellent properties such as low density, high strength, high hardness, corrosion resistance, high modulus, low thermal expansion coefficient, and oxidation resistance. Therefore, it has a wide range of applications in the fields of machinery, aviation, aerospace, military, electronics, electricity, and petrochemicals. However, as the requirements for the performance of SiC ceramics in related fields are increasing, its inherent brittleness and poor reliability have limited the long-term development of SiC ceramics in related fields. Therefore, it is necessary to prepare a SiC-based composite material with high toughness, high strength and excellent performance using SiC ceramics as the matrix.

[0004] The strengthening mechanisms of structural ceramic materials mainly include particle toughening, fiber and whisker toughening, stress-induced phase transformation toughening, etc. Researchers hope to improve the brittleness and overcome the mechanical properties defects of ceramic materials by making the above mechanisms occur inside the ceramic materials during the preparation and design stage. Fiber-reinforced ceramic matrix composites can improve the shortcomings of brittle fracture of single ceramic materials, improve the impact resistance of materials, and at the same time maintain the advantages of low density of materials, which has obvious advantages. Domestic and foreign scholars have adopted a series of fiber materials with high strength and high modulus such as SiC fiber, boron fiber, carbon fiber, graphite fiber and aramid fiber to compound with SiC ceramics. Studies have found that among the above fibers, carbon fiber and SiC fiber have the best reinforcement effect. They can give full play to the reinforcement mechanism of fiber deflection of cracks in the matrix and fiber debonding and fiber pull-out, and can consume the fracture energy in the matrix to the maximum extent, so that the brittleness of SiC ceramic materials is minimized. The carbon fiber reinforced SiC matrix composite (Cf / SiC ceramic) prepared by this method has high strength and toughness, and the physical and chemical properties can meet the requirements of high-temperature structural and functional materials.

[0005] At present, most of the research on the impact resistance of carbon fiber reinforced ceramics is aimed at coating woven fibers and layered intermixed woven fibers in ceramic materials. These coated and intermixed woven fibers can be regarded as a limiting boundary condition in the process of ceramic destruction, but do not play a role in preventing cracks in the cracking process of the ceramic matrix, so this does not fundamentally overcome the brittle defects of ceramic materials. Directly adding chopped fibers in the process of SiC ceramic molding has a simple manufacturing process, stable performance of the molded material, high specific strength, and can significantly improve the fracture toughness of the ceramic, which has a role in hindering the crack propagation in the process of ceramic destruction, which will also significantly improve its dynamic mechanical properties. Therefore, it is necessary to study the use of chopped carbon fibers to compound with SiC ceramics, and to prepare composite materials with uniform performance by uniformly and effectively dispersing the chopped carbon fibers. Carrying out basic work on the structural design and process optimization of chopped carbon fiber reinforced SiC-based ceramics plays a vital role in promoting the development of ceramic protective structures in my country. Summary of the invention

[0006] The invention provides a preparation method of chopped carbon fiber reinforced SiC ceramics, which has a great influence on the sintering densification of ceramics by adjusting the introduction mode of ceramic additives. The modified phenolic resin adopts boron-modified phenolic resin, and boron can selectively segregate at silicon carbide grain boundaries, reduce grain boundary energy, reduce the ratio of grain boundary energy to surface energy, and promote sintering; at the same time, the boron element can be dissolved in the silicon carbide lattice to generate lattice defects, which is helpful to improve the diffusion coefficient and promote the sintering densification of ceramics; carbon can reduce the oxide layer on the surface of silicon carbide micropowder, improve the surface energy of the micropowder, and improve the sintering driving force; the modified phenolic resin realizes the dispersion of boron and carbon at the molecular level, so that boron and carbon can be evenly coated on the surface of carbon fiber and silicon carbide micropowder, effectively exert the sintering promoting effect of boron and carbon, which is beneficial to the removal of pores inside the ceramic and improves the sintering density of the ceramic; in summary, the problems in the background technology are solved.

[0007] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0008] A method for preparing chopped carbon fiber reinforced SiC ceramics of the present invention comprises the following steps:

[0009] S1. Weigh the raw materials according to mass percentage: 80-95% silicon carbide powder, 0.5% chopped carbon fiber, 8.5% modified phenolic resin, 2.0-8.5% ceramic additive; the ceramic additive is analytically pure, including 10-20% dispersant, 45-55% binder, and 30-40% sintering aid; the modified phenolic resin is boron-modified phenolic resin;

[0010] S2, ultrasonically disperse the above-mentioned mass percentage of chopped carbon fibers, add the remaining raw materials into a ball mill, and add deionized water of the same mass as the raw materials, mix for 24 hours, and after ball milling evenly, add the ultrasonically dispersed chopped carbon fibers, and then continue ball milling for 10-20 minutes;

[0011] S3. After the ball milling, spray granulation is performed, and the granulation powder-water ratio is controlled to be 1.0-1.4%;

[0012] S4, pour the granulated powder into a conical mixer, mix and homogenize for 10 minutes, and bag the granulated powder and age it at room temperature for 24 hours;

[0013] S5. Use a four-column hydraulic press to press the ceramic green body, vacuum-pack the pressed ceramic green body, and place it in a cold isostatic press for cold isostatic pressing at a pressure of 150 MPa. After isostatic pressing, the green body density is 2.0 g / cm 3 ;

[0014] S6, placing the green body after isostatic pressing into a 150° C. oven and drying for 24 hours;

[0015] S7. The dried green body is placed in a vacuum sintering furnace for sintering at a temperature of 2200° C. for 3 hours. After being taken out, a chopped carbon fiber reinforced SiC ceramic product is obtained.

[0016] Furthermore, the silicon carbide powder is made of D 50 =0.704μm, D 97 =1.612μm, w(SiC)≥99.6%, w(SiO2)≤0.3% silicon carbide powder.

[0017] Furthermore, the length of the chopped carbon fiber is 2 mm.

[0018] Furthermore, the boron content of the modified phenolic resin is 8%, and the residual carbon rate is 35%.

[0019] Furthermore, the dispersant is triammonium citrate or ammonium polymethacrylate.

[0020] Furthermore, the binder is silicate or carboxymethyl cellulose.

[0021] Furthermore, the sintering aid is aluminum nitride or B4C.

[0022] Furthermore, the modified phenolic resin is prepared by adding boric acid to the phenolic resin, wherein the molar ratio of boric acid to phenolic resin is 7.5-8.5:1.5-2.5, controlling the temperature of the reactor at 85-115°C, stirring and mixing the mixture under alkaline catalysis, and after reacting for 2-3 hours, removing the reaction solvent and the catalyst to obtain a brown-red boron-modified phenolic resin.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention comprises silicon carbide powder, chopped carbon fiber, modified phenolic resin and ceramic additives; the modified phenolic resin is obtained by adding boric acid to phenolic resin; different carbon fiber dosages have a significant effect on the sintering density of ceramics; the introduction of ceramic additives has a great influence on the sintering densification of ceramics; boron can selectively segregate at the silicon carbide grain boundaries, reduce the grain boundary energy, reduce the ratio of grain boundary energy to surface energy, and promote sintering; and the boron element can be dissolved in the silicon carbide lattice to form lattice defects, which helps to improve the diffusion coefficient and promote the sintering density of ceramics; carbon can reduce the oxide layer on the surface of silicon carbide powder, increase the surface energy of the powder, and increase the sintering driving force;

[0025] (2) Boron is introduced in the form of boron carbide powder, and carbon is introduced in the form of carbon black and resin carbon. Due to the small particle size and large specific surface area of ​​carbon black, it is very easy to agglomerate, which makes it difficult to evenly distribute carbon black in the slurry. Agglomerated carbon black not only cannot promote uniform sintering of ceramics, but will inhibit the sintering densification of ceramics. Resin carbon is introduced in the form of organic polymers, which can be well integrated with the slurry medium. During the spray drying process, the resin can be evenly coated on the surface of silicon carbide powder. During the high-temperature sintering process, the resin carbon formed by cracking is evenly distributed on the surface of silicon carbide particles, which can better promote the uniform sintering of ceramics. By adjusting the introduction method of boron and carbon to boron Modified phenolic resin, adding boric acid to phenolic resin, the molar ratio of the two is 7.5-8.5:1.5-2.5, controlling the temperature of the reactor at 85-115°C, fully stirring and mixing under alkaline catalysis, after 2-3 hours of reaction, removing the reaction solvent and the catalyst, and obtaining a brown-red boron-modified phenolic resin; the resin is a modified phenolic resin in which boric acid reacts with phenolic hydroxyl groups in the resin to generate phenyl borate, and the resin achieves molecular-level dispersion of boron and carbon, so that boron and carbon can be evenly coated on the surface of carbon fiber and silicon carbide micropowder, effectively exerting the sintering promoting effect of boron and carbon, which is beneficial to the removal of pores inside the ceramic and improving the sintering density of the ceramic;

[0026] (3) Through experiments, it was verified that the flexural strength of the carbon fiber sample was increased by 13.7% compared with the flexural strength of the SiC ceramic without carbon fiber; while the carbon fiber / silicon carbide ceramic sample ensured the sintering density, the carbon fiber had a bridging effect inside the material, thereby improving its flexural strength. It is worth noting here that if the increase in carbon fiber content leads to a large number of defects inside the Cf / SiC ceramic, or the amount of residual carbon increases, the flexural strength of the material will decrease.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 A step diagram of a method for preparing chopped carbon fiber reinforced SiC ceramics according to the present invention;

[0030] Figure 2 Flowchart of the preparation of Cf / SiC ceramics for the experiments. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] After years of development, there are many molding methods and sintering methods for Cf / SiC ceramics made of short fibers and SiC matrix. We use the relatively mature molding method of Cf / SiC ceramics, the gel injection molding method, and the new sintering method that can densify and sinter Cf / SiC composite materials, the pressureless sintering method. The sintering process is relatively simple, and the comprehensive mechanical properties of pressureless sintered silicon carbide are better. The gel injection molding method is a material molding process developed by the United States in the 1990s. The gel injection molding operation steps are a molding method in which monomers, various additives such as cross-linking agents, dispersants, etc. are cured in situ by the action of initiators and catalysts. The first step: ultrasonically disperse the chopped carbon fibers; the second step: prepare the ingredients according to the formula, ball mill each powder for 24 hours, and after the ball milling is uniform, add the ultrasonically dispersed carbon fibers and ball mill for 10-20 minutes; the third step: pour the slurry into the mold, solidify it, and obtain the green body; the fourth step: low temperature drying the green body; the fifth step: vacuum sintering. This molding method is simple and mature, has low requirements on molds and operations, and can produce complex-shaped and high-strength green bodies with good uniformity, high density and high solid content.

[0033] See also Figure 1 As shown, a method for preparing chopped carbon fiber reinforced SiC ceramics of the present invention comprises the following steps:

[0034] S1. Weigh the raw materials according to mass percentage: 80-95% silicon carbide powder, 0.5% chopped carbon fiber, 8.5% modified phenolic resin, and 2.0-8.5% ceramic additive; the ceramic additive is analytically pure, including 10-20% dispersant, 45-55% binder, and 30-40% sintering aid; the modified phenolic resin is boron-modified phenolic resin; the silicon carbide powder is D 50 =0.704μm, D 97 =1.612μm, w(SiC)≥99.6%, w(SiO2)≤0.3% silicon carbide powder; the length of the short carbon fiber is 2mm; the boron content in the modified phenolic resin is 8%, and the residual carbon rate is 35%; the dispersant is triammonium citrate or ammonium polymethylacrylate; the binder is silicate or carboxymethyl cellulose; the sintering aid is aluminum nitride or B4C; the modified phenolic resin is specifically added with boric acid to the phenolic resin, the molar ratio of boric acid to phenolic resin is 7.5-8.5:1.5-2.5, the temperature of the reactor is controlled at 85-115℃, and the mixture is fully stirred and mixed under alkaline catalysis. After 2-3h of reaction, the reaction solvent and the catalyst are removed to obtain a brown-red boron-modified phenolic resin;

[0035] In this specific embodiment, preferably: 86% silicon carbide powder, 0.5% chopped carbon fiber, 8.5% modified phenolic resin, 5% ceramic additive; the ceramic additive is analytically pure, including 15% dispersant, 50% binder, and 35% sintering aid; the modified phenolic resin is boron-modified phenolic resin;

[0036] S2, ultrasonically disperse the above-mentioned mass percentage of chopped carbon fibers, add the remaining raw materials into a ball mill, and add deionized water of the same mass as the raw materials, mix for 24 hours, and after ball milling, add the ultrasonically dispersed chopped carbon fibers, and then continue ball milling for 10-20 minutes; the specific ball milling time in this specific embodiment is 15 minutes;

[0037] S3, after the ball milling is completed, spray granulation is performed, and the granulation powder-water ratio is controlled to be 1.0-1.4%; in this specific embodiment, the granule-powder-water ratio is 1.2%;

[0038] S4, pour the granulated powder into a conical mixer, mix and homogenize for 10 minutes, and bag the granulated powder and age it at room temperature for 24 hours;

[0039] S5. Use a four-column hydraulic press to press the ceramic green body, vacuum-pack the pressed ceramic green body, and place it in a cold isostatic press for cold isostatic pressing at a pressure of 150 MPa. After isostatic pressing, the green body density is 2.0 g / cm 3 ;

[0040] S6, placing the green body after isostatic pressing into a 150° C. oven and drying for 24 hours;

[0041] S7. The dried green body is placed in a vacuum sintering furnace for sintering at a temperature of 2200° C. for 3 hours. After being taken out, a chopped carbon fiber reinforced SiC ceramic product is obtained.

[0042] Performance Test:

[0043] The volume density of the sample was tested according to GB / T2997-2015 standard;

[0044] For each sample, two 3mm×4mm×46mm chopped carbon fiber reinforced SiC ceramic finished specimens were randomly prepared and the bending strength of the specimens was tested according to GB / T6569-2006 standard;

[0045] The preparation of Cf / SiC ceramics in this experiment includes the preparation of composite material slurry, slip casting, debonding, pressureless vacuum sintering and subsequent processing.

[0046] Different carbon fiber dosages have a significant effect on the sintering density of ceramics. Adjusting the introduction method of sintering aids has a great impact on the sintering densification of ceramics. Boron can selectively segregate at the silicon carbide grain boundaries, reduce the grain boundary energy, reduce the ratio of grain boundary energy to surface energy, and promote sintering. At the same time, the boron element can be dissolved in the silicon carbide lattice to produce lattice defects, which helps to increase the diffusion coefficient and promote the sintering density of ceramics. Carbon can reduce the oxide layer on the surface of silicon carbide micropowder, increase the surface energy of the micropowder, and increase the sintering driving force.

[0047] Boron is introduced in the form of boron carbide powder, and carbon is introduced in the form of carbon black and resin carbon. Since carbon black has a small particle size and a large specific surface area, it is very easy to agglomerate, which makes it difficult to evenly distribute carbon black in the slurry. Agglomerated carbon black not only fails to promote uniform sintering of ceramics, but inhibits the sintering densification of ceramics. Resin carbon is introduced in the form of organic polymers, which can be well integrated with the slurry medium. During the spray drying process, the resin can be evenly coated on the surface of silicon carbide powder. During the high-temperature sintering process, the resin carbon formed by cracking is evenly distributed on the surface of silicon carbide particles, which can better promote uniform sintering of ceramics. The introduction mode of boron and carbon is adjusted to be boron-modified phenolic resin, boric acid is added to the phenolic resin, the molar ratio of the two is 7.5-8.5:1.5-2.5, the temperature of the reactor is controlled at 85-115°C, and the mixture is fully stirred and mixed under alkaline catalysis. After 2-3 hours of reaction, the reaction solvent and the catalyst are removed to obtain a brown-red boron-modified phenolic resin; in this specific embodiment, boric acid is added to the phenolic resin, the molar ratio of the two is 8:2; the temperature of the reactor is controlled at 100°C, and the reaction time is 2.5 hours; the resin is a modified phenolic resin in which boric acid reacts with phenolic hydroxyl groups in the resin to generate phenyl borate, and the resin realizes the dispersion of boron and carbon at the molecular level, so that boron and carbon can be evenly coated on the surface of carbon fiber and silicon carbide micropowder, effectively exerting the sintering promoting effect of boron and carbon, which is beneficial to the removal of pores inside the ceramic and improving the sintering density of the ceramic. In this experiment, two groups of experiments were conducted on each sample, and the results were averaged, and the volume density was 2.592g / cm 3 .

[0048] The effect of adding carbon fiber on the flexural strength of SiC ceramics is shown in Table 2. As can be seen from the table, the flexural strength of the sample with added carbon fiber is 13.7% higher than that of SiC ceramics without carbon fiber. This is mainly because the Cf / SiC ceramic sample ensures the sintering density while allowing the carbon fiber to bridge inside the material, thereby improving its flexural strength. It is worth noting here that if the increase in carbon fiber content leads to a large number of defects inside the Cf / SiC ceramic, or an increase in the amount of residual carbon, the flexural strength of the material will be reduced.

[0049]

[0050]

[0051] Table 1: Sample density and flexural strength

[0052] Conclusion: The introduction of carbon fiber content will lead to internal defects in Cf / SiC ceramics or increase the amount of residual carbon, which closely affects the flexural strength of the material. The pressureless sintered Cf / SiC ceramics prepared with modified phenolic resin as sintering aid have excellent performance and its volume density is 2.592g / cm 3The flexural strength is 465MPa, which is 13.7% higher than the three-point bending strength of SiC ceramics without carbon fiber.

[0053] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing chopped carbon fiber reinforced SiC ceramics, characterized in that: The steps include: S1. Weigh the raw materials according to mass percentage: 80-95% silicon carbide powder, 0.5% chopped carbon fiber, 8.5% modified phenolic resin, 2.0-8.5% ceramic additive; the ceramic additive is analytically pure, including 10-20% dispersant, 45-55% binder, and 30-40% sintering aid; the modified phenolic resin is boron-modified phenolic resin; S2, ultrasonically disperse the above-mentioned mass percentage of chopped carbon fibers, add the remaining raw materials into a ball mill, and add deionized water of the same mass as the raw materials, mix for 24 hours, and after ball milling evenly, add the ultrasonically dispersed chopped carbon fibers, and then continue ball milling for 10-20 minutes; S3. After the ball milling, spray granulation is performed, and the granulation powder-water ratio is controlled to be 1.0-1.4%; S4, pour the granulated powder into a conical mixer, mix and homogenize for 10 minutes, and bag the granulated powder and age it at room temperature for 24 hours; S5. Use a four-column hydraulic press to press the ceramic green body, vacuum-pack the pressed ceramic green body, and place it in a cold isostatic press for cold isostatic pressing at a pressure of 150 MPa. After isostatic pressing, the green body density is 2.0 g / cm 3 ; S6, placing the green body after isostatic pressing into a 150° C. oven and drying for 24 hours; S7. The dried green body is placed in a vacuum sintering furnace for sintering at a temperature of 2200° C. for 3 hours. After being taken out, a chopped carbon fiber reinforced SiC ceramic product is obtained.

2. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The silicon carbide powder is made of D 50 =0.704μm, D 97 =1.612μm, w(SiC)≥99.6%, w(SiO2)≤0.3% silicon carbide powder.

3. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The length of the chopped carbon fiber is 2 mm.

4. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The boron content of the modified phenolic resin is 8%, and the residual carbon rate is 35%.

5. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The dispersant is triammonium citrate or ammonium polymethacrylate.

6. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The binder is silicate or carboxymethyl cellulose.

7. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The sintering aid is aluminum nitride or B4C.

8. The method for preparing chopped carbon fiber reinforced SiC ceramics according to claim 1, characterized in that: The modified phenolic resin is specifically prepared by adding boric acid to the phenolic resin, wherein the molar ratio of boric acid to the phenolic resin is 7.5-8.5:1.5-2.5, controlling the temperature of the reactor at 85-115°C, stirring and mixing the mixture fully under alkaline catalysis, and after reacting for 2-3 hours, removing the reaction solvent and the catalyst to obtain a brown-red boron-modified phenolic resin.

Citation Information

Patent Citations

  • Preparation method of reaction sintering silicon carbide ceramics with small residual silicon size and low residual silicon content

    CN106995314A

  • Silicon carbide ceramic material for optical system, reflective mirror, preparation method and sintering aid

    CN114249595A

  • Method for preparing fiber-toughened silicon carbide ceramic valve through pressureless solid-phase sintering compression molding

    CN116924808A

  • Method for preparing fiber toughened silicon carbide ceramic valve through reactive sintering compression molding

    CN116924809A

  • Method for preparing fiber-toughened silicon carbide ceramic valve through liquid-phase sintering compression molding

    CN116924810A